The Collected Works of James Wm. McClendon, Jr. : Volume 1 - McClendon, James Wm., Jr., (James William), 1924-2000 (Book collections on Project MUSE., 2014)
James Wm. McClendon, Jr. was the most important "baptist" theologian of the twentieth century. McClendon crafted a systematic theology that refused to succumb to the pressures of individualism, grew out of the immediacy of preaching the text, and lamented the stunted public witness of a fractured Protestant ecclesiology.This two-volume set mixes previously unpublished and published lectures and essays with rare and little known works to form a representative collection of the essential themes of McClendon's work. The first volume focuses on the philosophical and theological shifts leading to M.